AR MENDORONG TRANSFORMASI DIGITALISASI DEEP LEARNING - Para Mitta Para Purbosari; Nurratri Kurnia Sari; Annisa Rohimatul Nur Hasanah (Universitas PGRI Madiun, 2026)
Advances in digital technology have driven the use of Augmented Reality and Deep Learning as innovations that support the transformation of learning in the modern educational era. This study aims to analyze the role of integrating AR and Deep Learning in improving the quality of learning, particularly in elementary education. The method used is a Systematic Literature Review (SLR), which involves identifying, selecting, evaluating, and synthesizing relevant scientific articles from various reputable databases. The results of the study indicate that AR can enhance the visualization of learning materials, learning motivation, student engagement, and conceptual understanding through interactive learning experiences. Deep Learning plays a role in supporting adaptive learning by analyzing student data so that instruction can be tailored to individual needs. The integration of these two technologies creates a more effective, personalized, and meaningful learning experience, while also supporting the development of 21st century competencies. However, their implementation still faces challenges related to infrastructure readiness, educator competencies, and resource availability. Therefore, collaboration among various stakeholders is needed to optimize the application of AR and Deep Learning in education.